Matter of pride ; A mental case ; Regine in season [videorecording] - Lazaro, Cheche (Quezon City Probe Productions)
A story about the SEA Games preparation for the 1991 hosting of the Philippines. A look at the National Mental Hospital reported fund mess. Regine Velasquez stages a concert at Ultra.
Matter of pride (18 min.) -- A mental case (16 min.) -- Regina in season (15 min.)
VHS.
Keywords: Velasquez, Regine -- Interviews; Philippines. National Center for Mental Health -- Corrupt practices; Athletes -- Philippines; Mentally ill -- Care and treatment; Political corruption -- Philippines; Entertainers -- Philippines